Preliminary investigations on sun-hemp twine as a fishing net material - Miyamoto, H; Shariff, A T (Indian Journal of Fisheries, 2016)
The sun-hemp twine is an important net-making material in India next only to cotton and coconut fibre. Though the fishermen throughout the coastÂ line of India are using sun-hemp twines for gill-nets, boat-seines, beachÂ seines, ba-g-nets, stake-nets, etc., the characteristics of the twine as a fishing gear material have not yet been investigated. In these experiments, we have carried out a preliminary investigation on breaking strength, breaking stretch and rotting of the twines during continuous immersion in sea-water with a view to taking up further investigations on improving the twine as a gear material.